Kesiapan Bumdes Makmur Sejahtera Desa Jabalsari Kecamatan Sumbergempol Kabupaten Tulungagung untuk Mengimplementasikan Standar Akuntansi Keuangan Entitas Privat - Evi Widiastuti; Novi Khoiriawati (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to analyze the readiness of Village Owned Enterprises Makmur Sejahtera's accounting books, Jabalsari Village, Sumbergempol District, Tulungagung Regency based on Private Entity Financial Accounting Standards. This research is a qualitative research with a descriptive approach. Data were obtained using interviews and documentation and analyzed using the Miles and Huberman model. The results showed that the accounting books at Village Owned Enterprises Makmur Sejahtera, Jabalsari Village, Sumbergempol District, Tulungagung Regency did not refer to Financial Accounting Standards. The financial statements consist of statements of cash flow and profit and loss. Readiness of Human Resources, Finance, Regulations, Infrastructure and Technology shows that Village Owned Enterprises Makmur Sejahtera Jabalsari Village, Sumbergempol District, Tulungagung Regency is ready to implement Private Entity Financial Accounting Standards. Barriers to implementing Private Entity Financial Accounting Standards at Village Owned Enterprises Makmur Sejahtera Jabalsari Village, Sumbergempol District, Tulungagung Regency are the assumption that the application of Financial Accounting Standards has no effect on the company's financial condition and the lack of socialization about the application of financial accounting standards makes business actors still reluctant to apply Financial Accounting Standards in his efforts. Keywords: Accounting Bookkeeping, Private Entity Financial Accounting Standards